1979
DOI: 10.1104/pp.64.5.867
|View full text |Cite
|
Sign up to set email alerts
|

Gibberellic Acid Activates Chromatin-bound DNA-dependent RNA Polymerase in Wounded Potato Tuber Tissue

Abstract: Chromatin-bound DNA-dependent RNA polymerases react upon wounding of white potato tuber tissues with an increase in activity, which is additionally enhanced to 300% in the presence of0.1 micromolar gibberellic acid (GA3). 2,4-Dichlorophenoxyacetic acid is only weakly effective and indoleacetic acid not at aLL Wounding and treatment with GA3 affect template availability of chromatin only slightly. The hormone has no effect on chromatin-bound RNA polymerases, if added in vito. Wounding of plant storage tissues s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1979
1979
1991
1991

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 20 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…Nearest-neighbour frequency analysis of the RNA from resting and wounded tissues revealed that the quality of the RNA and hence the quality of transcription change after an injury [11]. The mechanism of this wound-induced activation of RNA synthesis is not clear, although hormones interfere with this process [ 11,22,30,31]. Gibberellic acid (GA3) if exogenously supplied to wounded tissues, enhances transcription over untreated controls.…”
Section: Introductionmentioning
confidence: 99%
“…Nearest-neighbour frequency analysis of the RNA from resting and wounded tissues revealed that the quality of the RNA and hence the quality of transcription change after an injury [11]. The mechanism of this wound-induced activation of RNA synthesis is not clear, although hormones interfere with this process [ 11,22,30,31]. Gibberellic acid (GA3) if exogenously supplied to wounded tissues, enhances transcription over untreated controls.…”
Section: Introductionmentioning
confidence: 99%
“…This activation process leads to a conditioned cell The present results clearly show that the synthesis of different RNA species and consequently the polyribosome formation are under control of GA3. The hormone is recognized by wounded tissue in a time-specific way, the signal is somehow transferred to the genome, and triggers the activation of gene transcription (39).…”
mentioning
confidence: 99%